Building the best portfolio for career progression. Issue 9 (September 2018) - Nesbitt, Craig; McCaslin, James
Abstract: This article outlines the author's recommendations on accomplishing the best surgical portfolio to support successful career progression. The key areas covered are research, education, quality improvement, management skills, leadership development, clinical/operative experience and external interests. The article is intended to guide trainees towards a more balanced portfolio and offers hints and tips on how to enhance the key areas of the portfolio that often go undervalued.